2015
DOI: 10.1007/s00467-015-3207-2
|View full text |Cite
|
Sign up to set email alerts
|

CFH gene mutation in a case of Shiga toxin-associated hemolytic uremic syndrome (STEC-HUS)

Abstract: We report a case of STEC-HUS with a quantitative CFH defect caused by a mutation of the CFH gene. To the best of our knowledge, very few cases of STEC-HUS with complement gene mutation have been reported, but none to date with a CFH mutation. We therefore suggest that complement analyses be performed in patients diagnosed with STEC-HUS in association with low C3 levels, especially in patients presenting with severe or unexpected clinical symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 31 publications
(81 reference statements)
2
5
0
1
Order By: Relevance
“…Still, when we focused our analysis on very rare pathogenic variants with minor allele frequency ,0.1%, we showed that such very rare pathogenic variants were associated with a fivefold higher risk of developing Shiga toxin-positive HUS. Thus, although Shiga toxin-associated HUS is mostly driven by the infectious agent, our study highlights that in rare cases, genetic abnormalities may contribute to complement activation in Shiga toxin-associated HUS, consistent with published data (9,10,(20)(21)(22)(23)(24)(25)(26)(27)(28). However, our study did not include patients with Shiga toxin infection who did not develop HUS (a study difficult to complete outside of large epidemics) and thus cannot prove the role of genetics in the risk of developing HUS after Shiga toxin infection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Still, when we focused our analysis on very rare pathogenic variants with minor allele frequency ,0.1%, we showed that such very rare pathogenic variants were associated with a fivefold higher risk of developing Shiga toxin-positive HUS. Thus, although Shiga toxin-associated HUS is mostly driven by the infectious agent, our study highlights that in rare cases, genetic abnormalities may contribute to complement activation in Shiga toxin-associated HUS, consistent with published data (9,10,(20)(21)(22)(23)(24)(25)(26)(27)(28). However, our study did not include patients with Shiga toxin infection who did not develop HUS (a study difficult to complete outside of large epidemics) and thus cannot prove the role of genetics in the risk of developing HUS after Shiga toxin infection.…”
Section: Discussionsupporting
confidence: 92%
“…Altogether, 17 children with postdiarrheal/Shiga toxin-producing Escherichia coli (STEC) HUS were subsequently reported who carried rare variants in complement genes (9,10,20-28). In nine of them, genetic screening was motivated by an unusually severe outcome, relapses, or post-transplant recurrence, suggesting that STEC infection triggers aHUS onset and/or preexisting complement variants amplify Shiga toxin-induced complement activation and endothelial/podocyte damage, and worsen disease severity (20)(21)(22)(23)(24)(25)(26)(27). However, seven reported patients who had complement variants had a favorable outcome (9,10,28), leaving the issue of the role of genetics in Shiga toxinassociated HUS unclear.…”
Section: Introductionmentioning
confidence: 99%
“…STEC-HUS does not usually recur, and a second bout of the disease should lead to the suspicion of alternative complement pathway dysregulation [260]. Patients develop antibodies that may, in part, be protective [101], but in the case of repeated exposition to Stx, recurrence has been described [261,262], for example with the atypical O80 serogroup [46].…”
Section: Recurrencementioning
confidence: 99%
“…Accordingly, two cases of STEC-HUS have been reported in a 4-year old child and an 18-month infant, both shown to carry MCP mutations. The outcome proved fatal in the former case while eculizumab resulted in protracted remission in the latter [11,12]. Similarly, Alberti et al reported two additional cases of STEC-HUS resulting in ESRD, yet, post-transplantation recurrence of HUS revealed a mutation of CFI and MCP respectively [13].…”
Section: Discussionmentioning
confidence: 98%